2022
DOI: 10.1186/s12912-022-00889-z
|View full text |Cite
|
Sign up to set email alerts
|

The level of spiritual care competence of Polish nurses and the psychometric properties of the spiritual care competence scale (SCCS)

Abstract: Background Providing effective spiritual nursing care requires development of professional competence which, when regularly evaluated, allows one to direct undergraduate and postgraduate nursing education in order to develop knowledge, skills and attitudes of nurses in the scope of spiritual care. Aim The aim of this study was to analyse the level of spiritual competence of professionally active nurses in Poland and, additionally, to analyse the ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
3
6
0
2
Order By: Relevance
“…The current study, which also investigated the relationships between demographic data and spiritual care competency, showed that postgraduate education and a longer working experience were linked to better spiritual care competency. The finding of a positive association between better spiritual care competency and a longer work experience was highly consistent with that in most previous studies [ 28 , 30 , 31 ], while postgraduate education was found to positively correlate with spiritual care competency in one report [ 28 ] but not investigated in the other two studies [ 30 , 31 ]. this may suggest that work experience may be an important universal factor associated with spiritual care competency of nurses.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The current study, which also investigated the relationships between demographic data and spiritual care competency, showed that postgraduate education and a longer working experience were linked to better spiritual care competency. The finding of a positive association between better spiritual care competency and a longer work experience was highly consistent with that in most previous studies [ 28 , 30 , 31 ], while postgraduate education was found to positively correlate with spiritual care competency in one report [ 28 ] but not investigated in the other two studies [ 30 , 31 ]. this may suggest that work experience may be an important universal factor associated with spiritual care competency of nurses.…”
Section: Discussionsupporting
confidence: 91%
“…With regard to comparing our results with those of previous studies, the present investigation showed a mean overall item score of 3.46 ± 0.60 out of a full score of 5 (i.e., percentage score: 69.20%), which was similar to that of a number of previous studies [ 28 – 31 , 33 , 35 , 45 ] that reported a percentage score ranging from 70% [ 45 ] to 77.3% [ 30 ]. While the previous studies covered a wide range of ethnic backgrounds and nurses from different health sectors [ 28 – 31 , 33 , 35 , 45 ], our results were closest to those of a study with the same ethnic background that reported a score of 70% despite its focusing on nurses of different subspecialties [ 45 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Some scales have been developed to evaluate the nurses’ competence, skills, and knowledge of spiritual care ( Machul et al, 2022 ). Daghan et al (2019) developed a scale for assessing the spiritual care competency of nurses with high reliability and validity.…”
Section: Introductionmentioning
confidence: 99%
“…In response to spiritual needs, the SC is considered to recognize what clients have not received. Spirituality and its nature in nursing are associated with the concept of competencies in SC and the integration of clients' S/R into practice, which are defined as the knowledge, skills, and attitudes required to develop SC [7]. Another definition maintains that competencies in SC and integration of clients' S/R into practice include nursing interventions or activities that help clients achieve physical, mental, social, and spiritual well-being [8].…”
Section: Introductionmentioning
confidence: 99%